RANTAI PEMASARAN HASIL USAHA BUDIDAYA MAGGOT (BELATUNG) SEBAGAI ALTERNATIF PAKAN TERNAK UNGGAS - Baiq Diah Fitasari; Baiq Santi Rengganis; Diah Meidatuzzahra; Fathurrahman Fathurrahman (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2021)
Feed plays a very important role in livestock business, both in terms of quality, quantity, and continuous availability. The biggest obstacle for farmers in running their business is the increasingly expensive feed price. Among the many alternatives in producing animal feed, insects are an alternative source of protein that can be used in animal feed. Maggot or larvae of the black soldier fly (Hermetia illucens) is a feed substitute as a source of protein. Market chain is a chain that is used to describe a number of networks that connect all related actors and transactions that occur in the movement of agricultural or livestock goods to final consumers (Lundy.et al, 2004:15). The purpose of this activity is to educate livestock groups in the promotive aspect to increase knowledge and apply it in marketing activities for maggot cultivation. Community service activities in the form of marketing counseling for maggot (maggots) cultivation as an alternative to animal feed in Mataram City were carried out on Saturday, August 21, 2021. This community service activity was carried out through counseling on discussion methods and presentations through lectures. Counseling is in the form of mapping the marketing of maggot and its impact if it is mass-cultivated. After giving the material, it was followed by discussion and question and answer from the participants.